2019
DOI: 10.1111/petr.13461
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy for severe portopulmonary hypertension in a child allows for liver transplantation

Abstract: Severe PPHTN is a contraindication to liver transplantation and predicts an abysmal 5‐year outcome. It is defined as a resting mPAP >45 mm Hg with a mean pulmonary artery wedge pressure of <15 mm Hg and pulmonary vascular resistance of >3 wood units in the setting of portal hypertension. There have been limited reports of successful treatment of PPHTN leading to successful liver transplantation in adults, and one reported use of monotherapy as a bridge to successful liver transplant in pediatrics. To our knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Combining two oral drugs may shorten the treatment time, but it is still more than half a year[16]. Combination with prostacyclins usually can get better results in a shorter time, especially for severe PoPH[17]. A multicenter study carried out in France showed that preoperative combination therapy can significantly reduce perioperative mortality, and whether to use combination therapy was the only independent risk factor affecting prognosis[18].…”
Section: Discussionmentioning
confidence: 99%
“…Combining two oral drugs may shorten the treatment time, but it is still more than half a year[16]. Combination with prostacyclins usually can get better results in a shorter time, especially for severe PoPH[17]. A multicenter study carried out in France showed that preoperative combination therapy can significantly reduce perioperative mortality, and whether to use combination therapy was the only independent risk factor affecting prognosis[18].…”
Section: Discussionmentioning
confidence: 99%
“…Limited pediatric case series and several adult studies have reported benefits of pulmonary vasodilator therapy for PPHTN with prostacyclin analogs, phosphodiesterase-5 inhibitors, and endothelin receptor antagonists. Hemodynamic response to combination therapy, including decreased PVR and mPAP, and increased cardiac index on evaluation by catheterization, has been documented as early as 3 months following initiation ( 9 , 10 , 23 ).…”
Section: Follow-upmentioning
confidence: 99%
“…Our pediatric cardiology experience of PPHTN is limited to case reports and series, which show variable but similarly high mortality rates up to 60%. Importantly, pediatric cases of PPHTN have been late diagnoses following the onset of symptoms and progression of disease, as children are not routinely screened for this entity (8)(9)(10)(11). However, the International Liver Transplant Society (ILTS) have provided a grade 1B recommendation for screening echocardiography for adult and pediatric liver transplant candidates with portal hypertension and a grade 1C recommendation for severe PPHTN to be considered an absolute contraindication to liver transplantation (12).…”
Section: Dr Khashayar Vakili (Liver Transplant Surgery)mentioning
confidence: 99%